(untitled) (Scientific journal of the Fergana State University, 2024)
This article pays special attention to ensuring the effectiveness of education through the effective use of pedagogical design methodology in the content of education, which is the driving force for the development of the state. Thoughts about the interest in the formation of design activities among schoolchildren and students in the modern educational process are highlighted. Changes in the existing content and methods of training future primary school teachers in higher education institutions based on new requirements, as well as approaches aimed at developing the pedagogical project competence of teachers and students will be discussed. The study also focuses on the design process and highlights various cases of it. For a deeper understanding of the design method, the guide will be discussed step by step. In this case, future primary school teachers should be asked about the importance of taking into account the cognitive abilities, interests and skills of students based on educational principles when organizing the process of teaching mathematics based on project-based methods. It is very important for future primary school teachers to take into account the cognitive abilities and interests of students and to develop skills based on educational principles when organizing the process of teaching mathematics based on design methods. It also describes how these processes are explained and addressed through pedagogical design competence.